Frequency of consumption and factors associated with hookah use in Curitiba, Brazil: a cross-sectional study - Heloisa Franco de Meira; Paulo Henrique Couto Souza; Juliana Schaia Rocha Orsi; Fernanda Tiboni; Sérgio Aparecido Ignácio; Constanza Andrea Hernandez Meza; Flávia Sukekava; Arieli Carini Michels; Amanda Dallegrave Vicentin; Patricia Lupion Torres; Emanuela Carla dos Santos; Mariana Hornung Marins; et al. (BMC Public Health)
Abstract Objective To analyze the consumption frequency and factors associated with hookah usage. Methods This cross-sectional study involved adults, hookah users, residing in the city of Curitiba. Hookah groups were contacted on social networking sites via an invitation that contained a link to the questionnaire, which comprised 21 questions covering demographic and socioeconomic characteristics, user profiles, use of cigarettes and alcohol, symptoms, and perceptions of the risks of hookah use. The dependent variables were low and high consumption frequency. Multivariate analysis was performed using the backward method with p ≤ 0.20 in the chi-square test, and variables with p ≤ 0.05 were included in the final model. Results Two hundred and seven questionnaires were included, and most hookah users were aged 22 years or older, resident in the south region, male, higher education, single, with high income, and categorized as low-consumption users. They started using hookah at up to 17 years old, discovered it through friends, purchased hookah essence from a tobacconist, and used it in groups, with 3 sessions or more per day, and the session duration was 50 min or more. They did not smoke conventional cigarettes, either during the hookah session or otherwise, and consumed alcohol during the hookah session, felt dizzy while using the device, and most believed that hookahs could harm their health. Higher values for high consumption compared to low consumption were observed in individuals aged up to 22 years, those with high school education, and those who purchase hookah essence from a distributor. High consumption was associated with individual use and the absence of symptoms when using hookah. Smoking conventional cigarettes during hookah session, experiencing dizziness, and reporting that symptoms disappeared after cessation of use were higher in the low-consumption group. Among high-consumption users, the majority resided in the northern region (Prevalence Ratio 6.736), were under 22 years of age (1.445) and bought essence from the distributor (1.463). Those who experienced dizziness (0.671) consumed hookah less frequently. Conclusion High consumption was associated with region, age, and place of purchase of essence, indicating that effective public policies necessitate formulating. Categories: Behavioral, Epidemiologic, and Health Services Research.